2020
DOI: 10.3390/ijerph17051613
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Risk Perceptions Related to Particulate Matter on Outdoor Activity Satisfaction in South Korea

Abstract: In recent years, the Korean public has become aware of the form of air pollution known as particulate matter, with a consequent growth of public anxiety causing a negative risk perception about outdoor activity. This study aims at determining the causal relationship between risk perceptions about particulate matter and outdoor activity satisfaction in South Korea. An Internet survey was conducted with 412 people, and a structural equation model was used to perform confirmatory factor analysis. The statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…All the measurement items were prepared based on the review of related literature and methods ( Table 2 ). For example, initial items for RP were generated following previous questionnaires conducted by Dionne et al [ 45 ] and Kim et al [ 53 ]. Measurement items of PU were compiled based on the infectious disease-specific health literacy scale [ 54 ] and the study by Qazi et al [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…All the measurement items were prepared based on the review of related literature and methods ( Table 2 ). For example, initial items for RP were generated following previous questionnaires conducted by Dionne et al [ 45 ] and Kim et al [ 53 ]. Measurement items of PU were compiled based on the infectious disease-specific health literacy scale [ 54 ] and the study by Qazi et al [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al determined the causal relationship between the risk perception of particulate matter and satisfaction of outdoor activities in South Korea, conducted an online survey of 412 people, and conducted confirmatory factor analysis using the structural equation model. The results showed that the perceived risk of particulate matter was higher when people had no interest or trust in public opinion or policy, which increased people's perception of health risks and, in turn, reduced their satisfaction with outdoor activities [ 22 ]. Zhao et al studied the Beijing-Tianjin-Hebei region as an example, used the Shapley value method to reasonably distribute the model benefits, construct the optimal emission reduction plan, and determine the optimal annual decision of each province.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PM risk perception is not only a real risk to health, but also a complex phenomenon affecting changes in public opinion and policy 53 . For example, Outdoor activity such as walking are limited by the level of particulate matter 54 .…”
Section: Discussionmentioning
confidence: 99%